Comments on the U (2) noncommutative instanton - Correa, D.H. (2001)
We discuss the 't Hoof ansatz for instanton solutions in noncommutative U (2) Yang-Mills theory. We show that the extension of the ansatz leading to singular solutions in the commutative case, yields to non self-dual (or self-antidual) configurations in noncommutative space-time. A proposal leading to selfdual solutions with Q = 1 topological charge (the equivalent of the regular BPST ansatz) can be engineered, but in that case the gauge field and the curvature are not Hermitian (although the resulting Lagrangian is real). © 2001 Published by Elsevier Science B.V.